2009
DOI: 10.1002/ppap.200900034
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Crystallinity on Polymer Interaction with Oxygen Plasma

Abstract: In order to study the role of polymer crystallinity, we performed oxygen plasma treatment experiments on amorphous and semicrystalline poly(ethylene terephthalate) (PET) polymers. The samples were treated in weakly ionized, highly dissociated RF oxygen plasma in glow region for different exposure times. We found that the degree of polymer crystallinity has an influence on the recombination probability of neutral atoms which interact with the surface. For amorphous polymers the recombination coefficient is in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 103 publications
(66 citation statements)
references
References 45 publications
5
53
0
Order By: Relevance
“…Junkar et al showed that amorphous PET was etched at a higher rate than semi-crystalline at the same conditions, so the formation of nanostructures of typical lateral dimension of almost 200 nm can be attributed to preferential etching of the amorphous phase. [33] These findings were confirmed also by DSC analysis, as plasma treated samples showed a higher crystalline content. Since the roughness did not increase substantially with increasing treatment time the etching selectivity using neutral particles found in the afterglow did not seem dramatic.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Junkar et al showed that amorphous PET was etched at a higher rate than semi-crystalline at the same conditions, so the formation of nanostructures of typical lateral dimension of almost 200 nm can be attributed to preferential etching of the amorphous phase. [33] These findings were confirmed also by DSC analysis, as plasma treated samples showed a higher crystalline content. Since the roughness did not increase substantially with increasing treatment time the etching selectivity using neutral particles found in the afterglow did not seem dramatic.…”
Section: Resultssupporting
confidence: 76%
“…The material is rapidly functionalized using oxygen-containing gaseous plasma created by different discharges. Although numerous authors have addressed the scientific issues on interaction of gaseous plasma with PET materials [33][34][35][36][37] the role of different reactive plasma particles in surface modification is still not well understood. A reason for a poor understanding of phenomena is that plasma contains a variety of particles capable of modification of PET surfaces and synergistic effects might play a dominant role.…”
Section: Introductionmentioning
confidence: 99%
“…The morphological features further developed with prolonged treatment as the temperature of the samples increased. As explained elsewhere, prolonged treatment causes an increase in sample temperature reaching close to melting point; thus, small features tend to agglomerate to larger ones [22]. In Figure 4, we can observe that the size of the features was rather varied; from smaller, with diameter of less than 1 µ m after 10, 20 and 40 s of treatment, to larger, with diameters of a few µ m after 80 and 160 s of treatment-the lateral size of dots thus gradually increased with treatment time.…”
Section: Resultsmentioning
confidence: 99%
“…Namely, the interaction between neutral oxygen atoms and organic materials is extremely selective. It has to be pointed out that even chemically identical materials are etched at different rates upon exposure to oxygen plasma [84]. In the cited reference [84] major differences in the behaviour of PET polymer with different degrees of crystallinity were reported.…”
Section: Plasma Treatment Of Cellulose Wound Dressingmentioning
confidence: 99%